Strategies and tactics of the Moro Islamic Liberation Front (MILF) in the Southern Philippines - Taya, Shamsuddin L. (Universiti Utara Malaysia, 2009)
This book reveals the strategies and tactics of the Moro Islamic Liberation Front (MILF) in the Southern Philippines. It looks at the political, military and economic strategies and tactics of the MILF in its quest to liberate the Bangsamoro homeland and its people from the clutches of the Government of the Republic of the Philippines (GRP) and its agents. Matenal for this work came from primary and secondary sources, namely newspapers, policy statements, speeches, press releases, joint communiqué, peace agreements, books, magazines, and journals. Interviews with informed people were also conducted. It was found that the strategies and tactics of the MILF in its quest for freedom and self determination of the Bangsamoro homeland and its people were effective and workable. The MILF as a splinter liberation movement had emerged as the dominant independence movement in the Southern Philippines. The strategies and tactics of the organization have not only guaranteed its survival, but they even led to its emergence as the most dominant and powerful liberation movement in the region. The MILF is now considered as a power to be reckoned with not only by the GRP, but also by both regional and international players.